Outcomes and Durability of Hepatic Reduction after Combined Partial Hepatectomy and Cyst Fenestration for Massive Polycystic Liver Disease - Chebib, Fouad T (J Am Coll Surg, 2016)
BACKGROUND: Partial hepatectomy and cyst fenestration (PHCF) selectively provides clinical benefit in highly symptomatic patients with polycystic liver disease (PLD). This study aims to ascertain whether the reduction in liver volume (LV) achieved by PHCF is sustained long term. STUDY DESIGN: Clinical data were retrieved from the electronic records of all patients with PLD who underwent PHCF between 1985 and 2014. Preoperative LVs (LV1), postoperative LVs (LV2), and late follow-up LVs (LV3) were measured from magnetic resonance or CT images. RESULTS: Among 186 patients who underwent PHCF, 91% were Caucasian women with autosomal dominant polycystic kidney disease with a mean age of 49 years. Major perioperative complications (Clavien III/IV) occurred in 21% of the patients. Operative mortality (<90 days) was 2.7%. Eleven patients had liver failure develop, received liver transplants, or had liver-related deaths. Overall survival was 95.7%, 93.3%, 85.6%, and 77.7% at 1, 5, 10, and 15 years respectively. Imaging records for volumetry were unavailable in 32 patients. Of the remaining 154 patients, 34 had imaging for 1 LV, 64 for 2 LVs, and 55 for all 3 LVs. Median LV was 6,781 mL (interquartile range 4,903 to 8,341 mL) preoperatively and 2,502 mL (interquartile range 2,089 to 3,136 mL) after PHCF, leading to a median postoperative LV reduction of 61%. At follow-up (mean 8 years), median LV was 2,519 mL (interquartile range 2,083 to 3,752 mL). Interestingly, 33 of 62 patients with available LV2 and LV3 showed additional regression in LV at follow-up (median –14.1%), and the rest showed mild growth of 9.9%. Overall volumetric comparison of preoperative with follow-up liver imaging showed sustained LV reduction (median 61%). CONCLUSIONS: Sustained long-term reductions in LV after PHCF can be achieved in selected patients with severe, highly symptomatic PLD. In our experience, liver-related death and subsequent liver transplantation are infrequent after PHCF.